Soul of money : reclaiming the wealth of our inner resources - Twist, Lynne (W. W. Norton, 2017)
Examines the link between our attitudes toward money--earning it, spending it, and giving it away--and our feelings of fulfillment, sufficiency, and purpose in our lives. This reissue includes a foreword by Jack Canfield and a new introduction by the author, in which she explores the effects of the Great Recession and environmental concerns about our monetary needs and aims.